On not abandoning church theology: Dirk Smit on church and politics - DeGruchy, SM (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
This essay argues for the importance of correctly defining, and then defending the concept of ‘church theology’ in dialogue with the thought of Dirk Smit. This is done by identifying and examining the ecclesiologies of the two trajectories that dominated the church’s opposition to apartheid in South Africa, namely Kairos and Belhar. The former, rooted in the notion of the church as Institution, came to expression in the Kairos Document which was highly critical of ‘church theology’. The latter, rooted in the Reformation understanding of the church, came to expression in the Belhar Confession which sought to clarify what it meant to be the church. Through the insights of Smit, a crucial theologian in the Belhar process, the essay argues that we need to find ways to draw these two divergent trajectories together and to recover the heart of what it means to do ‘church theology’ in our context today.